Targeting cancer cells through antibiotics-induced mitochondrial dysfunction requires autophagy inhibition. (1st January 2017) - Esner, Milan; Graifer, Dmitry; Lleonart, Matilde E.; Lyakhovich, Alex
Abstract: A significant part of current research studies utilizes various cellular models which imply specific antibiotics-containing media as well as antibiotics used for clonal selection or promoter de/activation. With the great success of developing such tools, mitochondria, once originated from bacteria, can be effectively targeted by antibiotics. For that reason, some studies propose antibiotics-targeting of mitochondria as part of anticancer therapy. Here, we have focused on the effects of various classes of antibiotics on mitochondria in cancer and non-cancer cells and demonlow mitochondrial membrane potential, reduced ATP production, altered morphology and lowered respiration rate which altogether suggested mitochondrial dysfunction (MDF). This was in parallel with increased level of reactive oxygen species (ROS) and decreased activity of mitochondrial respiration complexes. However, both survival and repopulation capacity of cancer cells was not significantly affected by the antibiotics, perhaps due to a glycolytic shift or activated autophagy. In turn, simultaneous inhibition of autophagy and treatment with antibiotics largely reduced tumorigenic properties of cancer cells suggesting potential strategy for anticancer therapy. Graphical abstract: Highlights: Cells exposed to antibiotics used in routine lab practice result in mitochondrial dysfunction. Antibiotics induce ROS-dependent autophagy/mitophagy in both normal and cancer cells. Cancer cells are not the perfect target for antibiotics, perhaps due to glycolitic shift. Cancer cells repopulation capacity can be reduced by antibiotics and inhibition of autophagy.